Use of Information and Communication Technology as Learning Media - Saputra, Erdiyan (Sunan Kalijaga International Journal on Islamic Educational Research, 2024)
The development of technology in the current era is very rapid, this directly changes people's needs and lifestyles, the development of information and communication technology includes two aspects, namely information technology and communication technology, in general information technology and communication technology for learning aims to make students understand technological devices information and communication in general, including computer (literacy) and information literacy, which means students recognize the terms used in information and communication technology. Information and communication technology is very necessary in learning in the current era. With the principles of using ticks that are effective and efficient, optimal, interesting and stimulate creativity, ticks have become one of the learning media that is widely used in various fields of education because it can increase effectiveness and efficiency in the learning process.